The Role Of Accounting Information Systems In Improving The Efficiency Of Financial Management Of The Nias Heritage Museum Foundation - Natalia Laoli; Dedi Irawan Zebua; Serniati Zebua; Noviza Asni Waruwu (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
Efficient financial management is a challenge for non-profit organizations, including the Nias Heritage Museum Foundation, which relies heavily on grants, donations, and non-commercial income. The main problem faced by the foundation is the use of Microsoft Excel for financial recording, resulting in reporting processes that take 3–7 working days, a high risk of input errors, lack of internal controls, and limited real-time data access. These conditions hinder the efficiency, transparency, and accountability of the foundation’s financial management.This study aims to analyze the role of Accounting Information Systems (AIS) in improving financial management efficiency at the Nias Heritage Museum Foundation. The research adopts a qualitative descriptive approach, with data collected through interviews, direct observation, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing stages.The results show that although the Excel-based AIS provides flexibility in recording and reporting, it has significant limitations, including the absence of automation features, minimal integration between divisions, and the risk of data loss due to local storage. The current AIS plays a role in supporting transaction recording, report preparation, financial control, and improving accountability to both internal and external parties. However, its role is not yet optimal due to reliance on manual input and technological constraints.The study concludes that the AIS used by the Nias Heritage Museum Foundation has provided a basic contribution to smooth financial administration but has not yet achieved maximum efficiency. To improve performance, it is recommended to adopt an integrated application-based AIS, provide staff training, strengthen internal controls, and implement cloud-based data storage systems. These measures are expected to accelerate reporting processes, reduce errors, and enhance the foundation’s transparency and accountability in the long term.